Associations between the peripheral blood Wilms tumor gene 1 level and both bone marrow blast cells and the prognosis in patients with myelodysplastic syndrome. Issue 3 (23rd February 2019) - Mashima, Kiyomi; Ikeda, Takashi; Toda, Yumiko; Ito, Shoko; Umino, Kento; Minakata, Daisuke; Nakano, Hirofumi; Morita, Kaoru; Yamasaki, Ryoko; Kawasaki, Yasufumi; Sugimoto, Miyuki; Ashizawa, Masahiro; et al.
Abstract: Wilms tumor gene 1 (WT1) is highly expressed in myelodysplastic syndrome (MDS) cells and is known to reflect the tumor burden in MDS. We evaluated the usefulness of WT1 mRNA levels for predicting the prognosis of MDS. At diagnosis, WT1 levels were strongly correlated with the percentage of blasts calculated based on non-erythroid cells, but not with that based on all nucleated cells ( r  = 0.57, p  < .05 vs r  = 0.42, p  = .13). Among the allogeneic transplant recipients, the presence of two consecutive WT1 levels ≥100 copies/μg RNA with a median interval of one month was associated with a 77.8% relapse rate at nine months from the first detection of a high WT1 level, and the median time to relapse was only 114 [36–257] days. WT1 levels at diagnosis were correlated with known prognostic factors. In addition, the presence of two consecutive high WT1 levels after allogeneic transplantation may predict early relapse of MDS.